Euphorbia telanganensis (Euphorbiaceae), a new species from Eastern Ghats of Telangana, India - Sadasivaiah, B.; Ramakrishna, A.; Prasad, K.; Devi, N. Sarojini; Rao, Nirmala Babu (Phytotaxa, 2022)
Euphorbia telanganensis (Euphorbiaceae), a new species is described and illustrated from dry deciduous forest of Amrabad Tiger Reserve, the Eastern Ghats of Telangana state. The present new species is similar to Euphorbia jodhpurensis but differs in obovate or elliptic-obovate or ovate-elliptic, abaxillay pubescent leaves, 1.5–2.2 mm long peduncle, turbinate involucre, ellipsoid glands, unequal gland limbs, shallowly undulate posterior limbs, capsules deeply keeled, and trigonous.